Assessing the post-treatment therapeutic effect of tongxie in irritable bowel syndrome: A randomized controlled trial. (September 2022) - Lai, Yaoliang; Liang, Xiao; Fan, Heng; Liu, Yujin; Zheng, Liang; Lu, Weimin; Sun, Yuling; Huang, Dawei; Liu, Xingxing; Zhang, Lijian; Zuo, Dongmei; Shou, Zhexing; et al.
Abstract: Diarrhea predominant irritable bowel syndrome (IBS) is a highly relapsing gastrointestinal disorder decreasing the quality of life. Existing studies indicated that the therapeutic effects maintained for a period of time after the treatments were discontinued (post-treatment therapeutic effects or PTTE). In this study, we aim to assess the PTTE of tongxie. We performed a multiple center, controlled, double blind study of patients with IBS randomized to tongxie (n = 120) or placebo (n = 120) for 4 weeks and followed up for 57 weeks. The primary outcomes were abdominal pains and stool consistency. The secondary outcomes were pain frequency and stool frequency. Tertiary outcomes were adverse effects and global overall symptom. The outcome data were collected at days 1, 2, 3, weeks 1 and 4 during the treatment and at days 1, 2, 3, until week 57 during the post-treatment. Significantly more patients receiving tongxie were clinical responders to the primary and secondary endpoints from day 1 until the end of the treatment. The positive effects of tongxie were maintained until 17–25 weeks after tongxie was discontinued. The relapse-free probabilities in the tongxie group were significantly higher than those in the placebo group ( P < .001). Twenty-five weeks after the therapies were discontinued could be considered as IBS natural history. During this period, an average of 53.8–56.3% of patients (pool tongxie and placebo data together) had IBS symptoms (pain scale ≥ 3, stool consistency ≥ 5). In particular, at the end of this study (week 61), 145 (54.2%) patients had IBS symptoms. Our results provide clinical insights into efficient and cost-effective management of refractory IBS, and lend support to the IBS management that the selection of a therapy should consider both its effectiveness during treatment and its PTTE after the treatment. Highlights: Irritable bowel syndrome (IBS) is most characterized by its high relapsing. Therefore, how long the therapeutic effects might maintain after the treatment* to prevent IBS from relapsing is equally important to how effective the therapy itself. Studies to investigate the PTTE are scarce. To accurately assess PTTE, a study should i) test simultaneously whether the treatment is effective when compared with a placebo, ii) follow up with patients for a period that is long enough to cover both the PTTE period, if any, and IBS natural history thereafter, iii) collect data at an adequate resolution. This study satisfies this 3-element criterion. This trial collected the outcome data both during tongxie treatment (4 weeks) and after the treatment (57 weeks).